2011
DOI: 10.3168/jds.2010-3678
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and further characterization of Arcanobacterium pyogenes isolated from bovine mastitis and from various other origins

Abstract: The present study was designed to identify phenotypically and genotypically 61 Arcanobacterium pyogenes isolated from bovine mastitis and from various other origins. The A. pyogenes isolates showed the typical cultural and biochemical properties of this species and displayed CAMP-like synergistic hemolytic activities with various indicator strains. The species identity could be confirmed genotypically by amplification and sequencing of the superoxide dismutase A encoding gene sodA of reference strains represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 20 publications
8
60
0
2
Order By: Relevance
“…Both the nanH and nanP genes also occurred in all isolates recovered from the uterus of dairy cows (Silva and Lobato, 1999). In contrast, other studies reported that the nanH gene was present only in 20.2% (Zastempowska and Lassa, 2012) and 87% (Hijazin et al, 2011) of isolates of bovine mastitis samples. Furthermore, 46 T. pyogenes isolates (92%) carried the fimA gene and most of them (82%) simultaneously harboured the fimC gene, while fimG was found in 38% of the isolates.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Both the nanH and nanP genes also occurred in all isolates recovered from the uterus of dairy cows (Silva and Lobato, 1999). In contrast, other studies reported that the nanH gene was present only in 20.2% (Zastempowska and Lassa, 2012) and 87% (Hijazin et al, 2011) of isolates of bovine mastitis samples. Furthermore, 46 T. pyogenes isolates (92%) carried the fimA gene and most of them (82%) simultaneously harboured the fimC gene, while fimG was found in 38% of the isolates.…”
Section: Discussionmentioning
confidence: 47%
“…Pyolysin (plo) is a major virulence factor, which is responsible for the lysis of host cells (Jost and Billington, 2005). The presence of the plo gene was demonstrated in all T. pyogenes strains of various origin (Silva and Lobato, 1999;Santos et al, 2010;Hijazin et al, 2011;Zhao et al, 2011). The plo gene was also detected in all of our T. pyogenes strains isolated from bovine mastitis cases.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Obtained Sequences were blasted with the GenBank NCBI nr database (http://www.ncbi.nlm.nih.gov/). The highest identity was selected as the identified and according to the results, sequences were submitted for species assignment (Hijazin et al 2011).…”
Section: Antibiotic Susceptibility Test:-mentioning
confidence: 99%